2020
DOI: 10.1515/opli-2020-0027
|View full text |Cite
|
Sign up to set email alerts
|

Do Sibilants Fly? Evidence from a Sound Symbolic Pattern in Pokémon Names

Abstract: Ancient writers, including Socrates and the Upanishads, argued that sibilants are associated with the notions of wind, air and sky. From modern perspectives, these statements can be understood as an assertion about sound symbolism, i.e., systematic connections between sounds and meanings. Inspired by these writers, this article reports on an experiment that tests a sound symbolic value of sibilants. The experiment is a case study situated within the Pokémonastics research paradigm, in which the researchers exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Some previous Pokémonastics experiments had been advertised on the same website (e.g. Kawahara, Godoy & Kumagai 2020), and 124 participants reported that they had either taken part in another Pokémonastics experiment or had studied sound symbolism before. Three participants were non-native speakers of Japanese.…”
Section: Participantsmentioning
confidence: 99%
“…Some previous Pokémonastics experiments had been advertised on the same website (e.g. Kawahara, Godoy & Kumagai 2020), and 124 participants reported that they had either taken part in another Pokémonastics experiment or had studied sound symbolism before. Three participants were non-native speakers of Japanese.…”
Section: Participantsmentioning
confidence: 99%
“…Previous studies have shown that increasing the number of choices to four in forced-choice tasks may decrease the chance of participants answering accordingly to the expected response (Aveyard 2012). Finally, in all the experiments reported by Kawahara et al (2020) and Kawahara et al (submitted), the flying aspect of the characters was highlighted by the fact that they were always presented in contrast with non-flying Pokémon. In the instructions, participants were told to pay attention to the fact that there were different types of Pokémon, and during the experimental trials, Pokémon were explicitly labelled as "normal Pokémon" and "flying Pokémon" (see an approximation of this experimental setting in Figure 3).…”
Section: Discussionmentioning
confidence: 85%
“…The findings by Kawahara & Kumagai (2019b) and Kawahara et al (2020) were later replicated with English speakers (Kawahara et al submitted). These studies open up a new opportunity to address which sound symbolic patterns are universal and which are language-specific (see above, as well as Iwasaki et al 2007 andSaji et al 2013 for language-specific symbolic associations), a topic of study that, as reviewed above, may shed light on how sound symbolism develops during language acquisition (Imai & Kita, 2014;Kantartzis 2011), what role it might have played in language evolution and communication (Perlman & Lupyan, 2018) and what the physiological and physical roots of these associations are (Morton 1994;Ohala 1994).…”
Section: Sound Symbolism In Pokémon Namesmentioning
confidence: 81%
See 2 more Smart Citations